2013
DOI: 10.4314/jae.v16i1.12
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation Strategies to Climate Change by Food Crop Farmers in Oke-Ogun Area of South Western Nigeria

Abstract: The study examined

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…However, Oyo State revealed the highest number of female farmers, probably due to the type of farming activities in the state. This agreed with the studies of Ayanwuyi et al (2010), Sangotegbe et al (2012) and Oluwasusi and Tijani (2013) that reported more farming activities by males than their female counterparts in Ekiti state. The male dominance could be attributed to the strenuous activities involved in a crude traditionally operated farming system.…”
Section: Demographic Characteristics Of the Respondentssupporting
confidence: 92%
See 1 more Smart Citation
“…However, Oyo State revealed the highest number of female farmers, probably due to the type of farming activities in the state. This agreed with the studies of Ayanwuyi et al (2010), Sangotegbe et al (2012) and Oluwasusi and Tijani (2013) that reported more farming activities by males than their female counterparts in Ekiti state. The male dominance could be attributed to the strenuous activities involved in a crude traditionally operated farming system.…”
Section: Demographic Characteristics Of the Respondentssupporting
confidence: 92%
“…More young people were involved in farming in Lagos State compared to other states. This could be attributed to incentives such as loan facilities being provided by the government, modern agricultural equipment and demand for farm produce(Apata et al, 2009;Ayanwuyi et al, 2010;Sangotegbe et al, 2012). Furthermore, Oluwasusi and Tijani (2013) observed that 89.4% of the farmers fell within 41 and 70 years.…”
mentioning
confidence: 99%
“…Several studies have shown the impact of climate change on maize using different climate change scenarios and crop simulation models in SSA 38 41 . In Nigeria, some studies have examined impacts of climate change on maize production and productivity resulting in several adaption strategies being promoted to reduce the negative effects of climate change 2 , 42 – 45 . Although several drought-tolerant maize varieties have been released for cultivation in the Nigerian savannas, no study has compared the impact of climate change on these varieties relative to the non-drought-tolerant ones.…”
Section: Introductionmentioning
confidence: 99%
“…This occurs in line with the historical, economic and political contexts in which they take place. In recent decades, farmer-herder conflicts in many parts of Sub-Sahara Africa have escalated into widespread violence, loss of property, destruction of farms, massive displacement of people, and loss of lives (ACAPS, 2017;Adelakun et al, 2015;Akov, 2017;Higazi, 2016;International Crisis Group, 2017;Sangotegbe et al, 2013). Kasarachi (2016) attributed causes to climate change, increasing pressure on resources, population pressure, decreasing efficiency of traditional conflict-management mechanisms, and the diversification of rural land use patterns including expansion of settled and ranching farming, national parks, towns and settlements.…”
Section: Introductionmentioning
confidence: 99%